Peningkatan Pemahaman Siswa Dalam Menentukan Luas Bangun Ruang Melalui Metode Driil Pada Siswa Kelas VI SDN 15 Laman Bukit - Asira, Asira (Jurnal Pendidikan Sosiologi dan Humaniora, 2020)
The general purpose of this study was to determine the ability and understanding to determine the area of building in class VI students at SDN 15 Laman Bukit in the subject of mathematics. Specifically, it is to describe 1) improvement of students 'understanding in determining the area of building in class VI students of SDN 15 Laman Bukit, 2) Describe the extent of the drill method to increase students' understanding in determining the area of building in grade VI students of SDN 15 Laman Bukit. The method used is Classroom Action Research and researchers as action actors. The subjects of this study were the sixth grade students of SDN 15 Laman Bukit in the academic year of 2019/2020 as many as 16 students consisting of 8 male students and 8 female students and mathematics class VI teachers who were also as researchers. The procedure of conducting Indonesian Language learning research uses audio visual media through four stages, namely: a) planning, b) implementation, c) reflection and d) evaluation. Data collection techniques in research are non-test techniques in the form of cycles, questionnaires, and documentation. The cycle is done individually or in groups to find out and observe the development of students' mathematical abilities in the learning process which includes aspects of communication, cooperation, confidence, and empathy in conducting activities in the process of learning mathematics. The instrument used during the observation was a cycle worksheet. The score given on the cycle sheet uses a scale of 1 - 5. The results showed an increase in students' mathematical ability in groups in the process of learning mathematics increased from 19% in the initial conditions to 30% in cycle I and increased to 40% in Cycle II from the good category in cycle II increased to very good in cycle III.